Upaya Kepolisian Republik Indonesia Dalam Penanggulangan Tindak Pidana Perjudian Online - Diky Hikmatul Fittra (UIN Syarif Hidayatullah Jakarta, 2025)
Online gambling is one form of cybercrime and represents a persistent social problem that has proven difficult to eradicate across generations. This study aims to analyze the legal framework regulating online gambling offenses and the efforts undertaken by the Kuningan Police in combating such crimes. The research employs a juridical-empirical method, using both the statute approach and the case approach to examine relevant legal norms and their practical implementation. The findings show that the regulation of online gambling is stipulated in the Indonesian Criminal Code (KUHP). The Kuningan Police’s efforts to address online gambling include conducting community outreach programs, cooperating with local village officials, and performing routine patrols. However, the study also identifies several obstacles that hinder effective law enforcement, such as limited public awareness, difficulties in tracing online offenders, and insufficient coordination among law enforcement institutions. Consequently, the role of the police in handling online gambling cases remains less effective, highlighting the need for stronger inter-agency cooperation and enhanced technological capacity to counter this evolving form of cybercrime.